Effectiveness of an Immersive VR System for Construction Site Planning Education - Wang, Kun-Chi; Hsu, Liang-Yu (KSCE journal of civil engineering, 2024)
Virtual reality (VR) has been widely used in education and training, but few studies have used it in education on construction site planning. Accordingly, this study developed an immersive VR-based education system for construction site planning and evaluated it in classroom-based tests with 114 students. Statistical analyses revealed that the VR system improved students’ learning outcomes compared when conventional paper-based learning. Specifically, students with lower pretest subject knowledge achieved similar scores to top-ranked students after undergoing VR education. Moreover, VR education was more effective for learning concepts than it was for memorization. A single-source teaching approach was also more effective in improving learning outcomes than a multisource approach for VR learning. In summary, this study investigated three previously unexplored areas: targeting the ideal recipients for VR education and training, determining the appropriate problem types for VR education and training, and identifying the effectiveness of VR education and training for construction site planning.